Chinese internet companies cross-border mergers and acquisitions motivation and risk analysis - Jiangnan, He (2022)
China's Internet industry has snowballed in recent years, and many companies have explored overseas markets through cross-border mergers and acquisitions. However, there is little literature on how Chinese Internet companies should respond to overseas M&As' risks. To study cross-border M&As by Chinese Internet companies, this thesis first introduces the industry's current state. Afterward, it analyzes its characteristics, motives, and risks, taking into account 2015-2019 the 56 available cases of overseas M&As from the Pedata database. It concludes with sound suggestions on how Chinese Internet companies can deal with the corresponding risks and conduct overseas M&As.